2020
DOI: 10.1051/0004-6361/202037994
|View full text |Cite
|
Sign up to set email alerts
|

The tidal tails of Milky Way globular clusters

Abstract: We report on the search for overall kinematical or structural conditions that have allowed some Milky Way globular clusters to develop tidal tails. For this purpose, we built a comprehensive catalog of globular clusters with studies focused on their outermost regions and we classify the globular clusters in three categories: those with observed tidal tails, those with extra-tidal features that are different from tidal tails, and those without any signatures of extended stellar density profiles. When exploring … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 54 publications
1
28
0
Order By: Relevance
“…As far as we know, this is the first detection of an extended tidal stream associated to this nearby (d = 2.3 kpc, Harris 2010), old (age= 12.6 ± 0.7 Gyr, Correnti et al 2018) and metal-poor ([Fe/H] = −2.1, Husser et al 2016) globular cluster. The cluster is not included in the list by Piatti & Carballo-Bello (2020). Leon et al (2000) reported the detection of extra-tidal stars within 150 from the center of the cluster, with an hint of a tail reaching ±100 from the center, approximately oriented along the E-W direction, in broad agreement with our findings.…”
Section: Ngc 6397supporting
confidence: 91%
“…As far as we know, this is the first detection of an extended tidal stream associated to this nearby (d = 2.3 kpc, Harris 2010), old (age= 12.6 ± 0.7 Gyr, Correnti et al 2018) and metal-poor ([Fe/H] = −2.1, Husser et al 2016) globular cluster. The cluster is not included in the list by Piatti & Carballo-Bello (2020). Leon et al (2000) reported the detection of extra-tidal stars within 150 from the center of the cluster, with an hint of a tail reaching ±100 from the center, approximately oriented along the E-W direction, in broad agreement with our findings.…”
Section: Ngc 6397supporting
confidence: 91%
“…Despite the low eccentricity (e = 0.2) of the orbit in which E 3 is placed, this cluster has lost a remarkable fraction of stars compared to the rest of Galactic GCs with sim-ilar orbital parameters (Piatti & Carballo-Bello 2020). Its core radius is also comparable or larger than the ones observed in the other members of that same family of GCs, and dynamically looks like a more evolved cluster.…”
Section: Resultsmentioning
confidence: 88%
“…This process led to the formation of stellar streams or tidal tails, such as the ones generated by the disruption of Pal 5 (Odenkirchen et al 2003;Grillmair & Dionatos 2006;Kuzma et al 2015); one of the most extended structures observed among the ones generated by the family of Galactic GCs. In recent years, as new datasets have become available, it has been possible to unveil more of these low surface-brightness tails, making evident that this is a common feature in Galactic clusters and that their formation is a manifestation of their orbital parameters and dynamical evolution (see summary of detections and discussion in Piatti & Carballo-Bello 2020).…”
Section: Introductionmentioning
confidence: 99%
“…(9) to orbital properties; the current mass (log(M cls /M )), the ratio between the mass lost by tidal disruption to the total mass (M dis /M ini ), and the ratio of the age to the half-mass relaxation time to decide whether the internal dynamical evolution plays a role; the tidal radius (r t ) and the rotation strength (ξ, Sollima et al 2019) to connect Eq. ( 9) to the internal rotation itself, and the status of a globular cluster according to whether it has tidal tails, extratidal features different from tidal tails, or simply a King (1962) profile (Piatti & Carballo-Bello 2020). Figure 3 shows some of these plots.…”
Section: Analysis and Discussionmentioning
confidence: 99%